Rees-Poole, V S. Church Square, Pretoria. (date unknown) Pavilion drawings: East Island. 1.Tram pavilion & Bank Chambers (blueprint & parchment). 2.1Plan & sections. 2.2.Plan & elevations (blueprint & parchment). Details for concrete roof. - Rees-Poole, Vivian Sydney (My University, 2012)
Rees-Poole, V S. Church Square, Pretoria. (date unknown) Pavilion drawings: East Island 1.Tram pavilion & Bank Chambers (blueprint & parchment). 2.1Plan & sections. 2.2.Plan & elevations (blueprint & parchment). Details for concrete roof.
Church Square Pretoria. East Island1.Tram pavilion & Bank Chambers (blueprint & parchment). 735X410. 2.1Plan & sections. 2.2.Plan & elevations (blueprint & parchment) 995X710. Details for concrete roof.
Keywords: Rees-Poole, V S. Church Square, Pretoria. (date unknown) Pavilion drawings: East Island.1.Tram pavilion & Bank Chambers (blueprint & parchment). 2.1Plan & sections. 2.2.Plan & elevations (blueprint & parchment). Details for concrete roof.; Rees-Poole, V S. Church Square, Pretoria. (date unknown) Pavilion drawings: East Island.1.Tram pavilion & Bank Chambers (blueprint & parchment). 2.1Plan & sections. 2.2.Plan & elevations (blueprint & parchment). Details for concrete roof.